Assessment of mobile medical units functioning in Jharkhand, India - Kumar, Mithilesh; Kiran, Asha; Kujur, Manisha (International Journal Of Community Medicine And Public Health, 2017)
Background: The NRHM has identified Mobile Medical Units (MMUs) as a strategy for improving access. The principle behind MMUs is to reach underserved areas by taking healthcare to the doorstep of the people. The study aims and objectives are to assess the function of Mobile Medical Units in Jharkhand and to identify the factors influencing the utilization of MMU. Methods: Three districts were selected based on geographical distribution with Ranchi as central district; Khunti was nearby district, and Garhwa as far of district. In each district two MMUs were selected for assessment. From each district two blocks and from each block one campsite was randomly selected. From each Campsite five beneficiaries were randomly selected. Every third beneficiary who had availed services of MMU was interviewed. The exit interview of beneficiaries was undertaken at the site of MMU. The data were analyzed by using SPSS Software. Results: Frequency of MMU visit at 04 campsites in Khunti, 02 in Garhwa & 01 in Ranchi were once in a month. Sahiya (ASHA) & NGOs were the main source of information about schedule of MMU visit. Medicines were available at all the campsites of all study districts. Laboratory test facility was available at 04 campsites in Garhwa, 03 in Khunti and 02 in Ranchi district. X-ray facility was not available in all MMUs. Conclusions: Easy accessibility and free services were the main factors that influence the MMU utilization.